Analysis of the Impact of RMB Appreciation on China’s Economy - Si, Yuqi (International Journal of Global Economics and Management, 2024)
Due to the epidemic war and other causes, the global economic development effect is not good situation, China’s economy still maintains a strong development momentum, so many countries for the appreciation of the renminbi began to sound, improve the exchange rate which is undoubtedly a very favorable situation for our country, so this article would like to think that the motivation of the appreciation of the renminbi and the impact of the analysis of the summary and generalization of the elaboration.